The Application of Sharia Economic Principles in Educational Financial Management: A Review of Applications, Problems, and Solutions - Misbah, Ahmad (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2025)
Financial management in Islamic educational institutions continues to face challenges related to transparency, accountability, and compliance with Sharia principles. These conditions indicate the need for a more comprehensive approach to implementing values of justice, sustainability, and financial integrity. This study aims to analyze the application of Sharia economic principles in educational financial management and identify practical steps and implementation challenges. The research employs a systematic literature review of studies published between 2020 and 2024 that are relevant to Sharia-based financial management in educational institutions. The findings show that institutions applying Sharia principles tend to demonstrate more structured, transparent, and value-oriented financial systems. The study also reveals that human resource competence, leadership commitment, and external support are key factors influencing the successful implementation of Sharia principles. Additionally, the research identifies a gap between theoretical understanding and practical application, highlighting the need for clearer operational guidelines. The study concludes that an implementable model is essential to bridge Sharia principles with the practical demands of educational financial management. The main contribution lies in providing an applicative framework that can serve as a reference for Islamic educational institutions in strengthening Sharia-based financial governance.